PENERAPAN PEMBELAJARAN DENGAN PENDEKATAN INTEGRASI SAINS DAN AGAMA UNTUK MENINGKATKAN MOTIVASI BELAJAR IPA FISIKA SISWA - Laurenty, Fretycia; M. Rahmad, M. Rahmad; Yennita, Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: This research aimed to know difference of the students motivation science learning by application of learning by science integration and religion approach to increase students motivation physics learning on force and acceleration lesson. This type of research is quasi experimental, with the nonequivalent control group design. The subject of this ini research is students class VIII at SMPN 5 Pekanbaru, total of 60 students as divide into two class, experimental class and control class. The instrument of data in this research is questionare motivation ARCS, consist of Attention, Relevance, Confidance dan Satisfaction. The data in this research is a score of motivation before and after learning physics by implementation science integration approach and religion and analysis of the data uses descriptive analysis. Then, measured the improvement of the students motivation by Independent Sampel T Test. Score motivation of students at experimental class in high category with average score motivation changing is 13,66%, and the control class in the high category with average score motivation changing is 4,22%. Therefore, it can be concluded that by using science integration and religion approach able to improve students motivation physics learning.Key Words: Science integration and religion approach, Motivation.